Heavy metal resistance of microorganisms isolated from coal mining environments of Santa Catarina - Castro-Silva,Marcus Adonai (2003)
The coal mining activity is characterized by the generation of large amount of by-products. One of them is pyrite, which tends to acidify the water, solubilizing heavy metals. As a consequence the environment becomes acid and rich in heavy metals, selecting microorganisms able to survive in this condition, which are of great interest as bioremediation agents. This work describes the isolation and characterization of microorganisms from a coal mining area in Santa Catarina. These microorganisms comprised bacteria, fungi and yeasts resistant to zinc, nickel and cadmium.